Fungi in the Sands of Egyptian Pyramids is a Concern for Public Health - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2021)
Fungi are contaminating the dry sands at Egyptian pyramids, a tourist area in Cairo; the contaminating fungi include various yeast and mould species and some species are known opportunistic pathogens or respiratory allergens. Presence of opportunistic and pathogenic fungi in the sands of pyramids can pose a health risk to visitors due to contact with sand, via direct exposure, such as wind, inhaling of aerosols, contact or through drinking; and indirectly by exposure to contaminated surfaces. In this issue, Echevarría and Iqbal (2021) report several species of filamentous fungi and yeasts in the sands of pyramids. Some of the identified species develop several diseases, so people with weak immune systems will need to protect themselves. Thus, the present knowledge of the distribution of fungal contaminants in sand samples reveals the need to measure and regulate their presence in sands of pyramids at least in the environment with high numbers of immunocompromised people. The data could serve as the basis for initiating regulatory measures to control fungal contamination of sand for the benefit of public health.